Pendampingan Penghijauan untuk Kesejahteraan Masyarakat: Sejuknya Udara, Sehatnya Jiwa dalam Upaya Pelestarian Lingkungan di Desa Barugbug Kecamatan Padarincang - Ambo Rasyid Ratulangi; M. Nassir Agustiawan; Eli Apud Saepudin; Abdul Muid; Cindi Saputri; Anneira Azzahra; Zahra Sauzan; Zanuba Qotrun Nada; Nursinta; Cristin Natalia; Yeni Febriyanti; Ardhi Julfadhli; Gladisya Audita Azzahra; Sartika; Intan Nabila Azhar; Yuyun Yunengsih; Ferdy Setyawan (Jurnal Ragam Pengabdian, 2024)
This reforestation assistance program aims to improve the welfare of the people of Barugbug Village, Padarincang District, through environmental conservation efforts that involve the active participation of residents. This reforestation activity does not only focus on tree planting, but also on counseling and environmental education to increase residents' awareness of the importance of preserving nature. The results of this program are expected to provide long-term benefits, such as improved air quality, psychological well-being of the community, and sustainability of the local ecosystem. This program is also expected to be a model that can be replicated in other villages in an effort to create a cool, healthy and sustainable environment.